Nephrogenic adenoma of the ureter: Case report - BOZKURT, SÜHEYLA (SPRINGER, 2007)
Nephrogenic adenoma is a rare metaplastic benign lesion of urothelium in response to genitourinary tract procedures, chronic infection, trauma, urinary calculi and immunosuppressive therapy after renal transplantation. It has been reported to occur throughout the urinary tract especially, in the urinary bladder. We report a case of nephrogenic adenoma arising from the lower end of the right ureter with clinical and radiological features suspicious of carcinoma.
Keywords: immunohistochemistry; nephrogenic adenoma; nephrogenic metaplasia; ureter; CLEAR-CELL ADENOCARCINOMA; PROSTATIC URETHRA; METAPLASIA; FEATURES